Kaidah Al Masyghul La Yushghal Dalam Konteks Akad Musyarakah Mutanaqisah - Rusdi Rizki Lubis; Jaih Mubarok (Scimadly Publishing, 2023)
This article describes the principles of al-masyghul la yusyghal fiqh principles in one of the Islamic economic practices, namely the musyarakah mutanaqisah contract. The method used is descriptive literature by collecting various literature related to the object of study. This research tries to explore the law of musyarakah mutanaqisah contracts which are commonly used in sharia banking in Indonesia in relation to their legal status using one of the rules of fiqh. This research concludes that the musyarakah mutanaqisah contract is no different from the rules of al-masyghul la yusyghal fiqh because in principle these fiqh rules can only be applied to provisions if the law of origin of an object changes its nature and position. This is also in accordance with DSN-MUI fatwa Number 73 of 2008 concerning Musyarakah Mutanaqisah and DSN-MUI Decree Number 1 of 2013 concerning Guidelines for Implementing Musyarakah Mutanaqisah in Financing Products.